An Analysis of the Role of the Male and Female District Hearing Officers and the Effectiveness of this Role - Hernandez-Segura, Yolanda; Kupczynski, Lori; Mundy, Marie-Anne; Ruiz, Alberto (Advances in Social Sciences Research Journal, 2015)
The Texas Education Code (TEC) contains a provision called “Safe Schools” that holds that students who exhibit discipline and behavioral problems may be suspended from school, removed to a disciplinary alternative education program, or expelled and placed in a juvenile justice alternative education program. The TEC mandates that before students are subjected to these disciplinary measures, each student must be provided with a due process hearing. At most independent school districts (ISDs) in South Texas, the Hearing Officers are responsible for facilitating the due process procedures. However, one problem at hand is that there are no formal guidelines, legal or administrative, that clearly define the case management approaches to be followed by the Hearing Officer. Notably, such approaches can provide guidance to Hearing Officers about the appropriate measures to take in balancing discipline and the educational needs and outcomes of at-risk youths; in respecting and upholding the dignity of the student being disciplined; and in ensuring that such students learn from the consequences of their school violations. Using the single case study approach, this study analyzed Hearing Officers’ duties, effectiveness in carrying out such duties, and whether gender had an impact on their performance.